Ecosystem services in Jiangsu province: Changes in the supply and demand patterns and its influencing factors - Wen, Yuling; Li, Hongbo; Zhang, Xiaolin; Li, Tingyun (Frontiers in Environmental Science, 2022)
Revealing the temporal and spatial evolution characteristics and key factors driving the relationship between the supply of and demand for ecosystem services (ES S&D) is paramount for the effective management of regional ecosystems and the rational allocation of natural resources. This study calculated the supply of ecosystem services (ESS) in Jiangsu Province, China, in 2000, 2010, and 2020, and quantitatively evaluated the ecosystem service demand (ESD) in those years by considering land development intensity, population density, and economic conditions. The ‘coupling coordination degree and relative development degree’ (CDRD) model is introduced to explore the degree of coordination and change in the relationship of supply versus demand of ecosystem services, and then to reveal the impact of various factors on the spatial differentiation characteristics of ES S&D. The results show that: (1) the ESS is high in the Taihu Lake Plain, the southwest of Huaihai area and the eastern coastal zone of Jiangsu Province, yet low in the northwest and middle of Huaihai area, and along the Yangtze River Plain. The overall distribution pattern of ESD and the coordinating degree of ES S&D is high in the south and north of Jiangsu Province but low in the province’s middle. (2) The degree of coordination between ES S&D increased from 0.371 to 0.415, and the relationship between supply and demand changed from one of moderate imbalance to one of basic coordination. The imbalance of supply and demand is mainly concentrated in the Lixiahe area, coastal plain area, and middle of the Huaihe River Basin, for which the predominant type is a moderate imbalance–demand lag. Meanwhile, the analysis of influencing factors shows that there is an obvious synergistic effect between different factors.